Nature-based solutions in coffee agroecosystems in Mexico: evaluation for adoption - Ruiz-García, Patricia; Monterroso-Rivas, Alejandro Ismael; Conde-Álvarez, Ana Cecilia (Frontiers in Sustainable Food Systems, 2025)
Nature-based solutions (NbS) are currently being developed in various coffee agro-ecosystems. However, not all actions can and should be considered NbS. For this reason, the objective of this study was to answer two research questions: What are the challenges (problems) and criteria (prerequisites for defining NbS) that NbS must meet in order to be considered in traditional coffee agroecosystems in Mexico? What indicators (measurable elements) can be used to evaluate the effectiveness of NbS? The method consisted of a rapid systematic review in three search stages. The first stage identified the global challenges and criteria established to date for an action to be considered NbS. The second stage focused on identifying the main NbS challenges and criteria that address the different coffee agroecosystems in Mexico. The third stage focused on identifying useful indicators to assess the effectiveness of nature-based solutions (NbS) in the Mexican coffee sector. Articles obtained at each stage were systematized using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement and analyzed using the Systematic Review Accelerator software, following Creswell’s framework. We found that shade coffee agroecosystems in Mexico currently address 12 NbS challenges (including integrated water management, climate resilience, environmental degradation or biodiversity loss) and meet 14 of the 18 NbS criteria. The type of agroecosystem management influenced the degree of compliance with the established criteria, so it is necessary to assess their effectiveness. This research proposes 48 indicators to evaluate the effectiveness of NbS in the Mexican coffee sector. The selection and adjustment of indicators made in this study can help to fill the information gap that currently exists in Mexico. NbS can contribute to mitigate the challenges facing Latin America and promote sustainable development. However, they require rigorous planning and management to ensure their effectiveness and durability, and policy makers are invited to look more closely at this issue.